Operation of the Appliances Based-Demand Response Modeling in Smart Buildings - Yabing Li; Shaojie Zhang; Huili Guo; Yanli Zhou (Journal of Artificial Intelligence and System Modelling)
At present, global energy consumption and emissions are largely dominated by non-renewable resources, particularly fossil fuels. As a result, there is a growing focus on investing in and researching alternative energy sources across various sectors, including residential buildings. Effective energy management in these structures can track real-time energy demand and appliance usage, leading to reduced energy bills and enhanced overall efficiency. This research examined the efficient functioning of appliances within smart homes, emphasizing the role of demand response (DR) in energy management for electrical grids. The efficient operation of these appliances is modeled based on household usage patterns, the capacity for demand flexibility in demand-side management (DSM), and energy pricing. The operation of the appliances is managed through a two-tier energy optimization process. In the first tier, energy usage is adjusted through DR and load shifting. The second tier focuses on reducing both consumption costs and consumer discomfort, taking into account the optimized energy usage established in the first tier. Finally, the efficiency of the two-layer energy optimization is confirmed by testing the proposed case studies in the numerical simulation.